BENTUK TOR-TOR BALANGSAHUA PADA MASYARAKAT DESA TANAH JAWA DI KABUPATEN SIMALUNGUN - dhiba inanta lubis (Universitas Negeri Medan, 2014)
The aim of this research is describing the form of Tor-tor Balangsahua dance at Javanese society in Simalungun.Theoretical foundation which is used in this research is theories related with the topic such as forming and dance element theories.The method used in this research is descriptive qualitative method. The collecting of data is done by field observing and interviewing to some informants to get data about Tor-Tor Balangsahua dance in Simalungun. The samples in this research are the man dancers an musicians in Tor-tor Balangsahua Dance.This research shows that, the form of Tor-tor Balangsahua dance related with movements like grasshopper act which is only for entertaining Simalungun society. Tor-tor Balangsahua dance has theme usihan or the dance which imitate animals movement. The movement in Tor-tor Balangsahua dance has four motives those are respectful move or sombah, flying move, move like grasshopper, and man dancers move. Musical accompaniment used is Haro-haro, and musical instruments are Ogung, Sarunei, and Gondrang. Making up used in Tor-tor Balangsahua dance is focused on man dancers. The costumes used by man dancers are Head cover or Destar, shawl on shoulder or Suri-suri, fabric from waist to toe or Hiou. Tor-tor Balangsahua dance uses proscenium stage. Keyword : Tor-tor Balangsahua.